2009
DOI: 10.1016/j.jacc.2008.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Neurologic Recovery in Patients With ST-Segment Elevation Myocardial Infarction Resuscitated From Cardiac Arrest

Abstract: When resuscitated patients with STEMI are being evaluated in the emergency department, serious consideration should be given to emergent angiography and revascularization, regardless of neurologic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 11 publications
5
55
2
3
Order By: Relevance
“…Result of our study clearly demonstrated improved survival with PCI in cardiac arrest patients, which were also shown in previous studies [5][6][7][8][9][10]24,25]. Statistical significant mortality benefit was also shown to be present in important subgroups including patients presenting with shock, without shock, patients with shockable rhythms (Vtach/Vfib), patients with non-shockable rhythms (Asystole/PEA), older patients (≥80 years ) and patients with high burden of comorbidities as indicated by CCI ≥ 2.…”
Section: Discussionsupporting
confidence: 90%
“…Result of our study clearly demonstrated improved survival with PCI in cardiac arrest patients, which were also shown in previous studies [5][6][7][8][9][10]24,25]. Statistical significant mortality benefit was also shown to be present in important subgroups including patients presenting with shock, without shock, patients with shockable rhythms (Vtach/Vfib), patients with non-shockable rhythms (Asystole/PEA), older patients (≥80 years ) and patients with high burden of comorbidities as indicated by CCI ≥ 2.…”
Section: Discussionsupporting
confidence: 90%
“…79,80 Access to PCI Up to 70% of patients with OHCA have coronary artery disease. Although 50% have acute coronary occlusion, [81][82][83][84][85][86][87][88][89][90][91] only a minority of patients with OHCA with ROSC who were transported to hospital have an ST-segment elevation on a 12-lead ECG. 92,93 Mortality after emergent angiography for STEMI patients in the setting of post-ROSC OHCA is greater than that in the setting of STEMI alone.…”
Section: Referring and Receiving Facilitiesmentioning
confidence: 99%
“…25 A number of other observational series have indicated high procedural success rates and in-hospital survival rates between 60% and 78%, with early coronary angiography for patients with STEMI after OHCA. 24,26,61,62 Although an urgent interventional approach for OHCA with STEMI is recommended, the role of urgent coronary angiography in patients with OHCA and non-STEMI is uncertain. Many clinicians may advocate waiting to assess neurological recovery before proceeding to angiography.…”
Section: Management Of Acute Coronary Syndrome In the Ohca Patientmentioning
confidence: 99%